Ternary block polybenzimidazole ion conducting membrane and preparation method thereof
The low conductivity of the polybenzimidazole ion conduction film is solved by using a ternary block polybenzimidazole copolymer resin and an organic solvent with an acid or alkali mixed solvent to form a hydrogen bond crosslinking network and an acid or alkali replacement flow field. The rate and stability issues achieve efficient ion conduction and excellent mechanical properties.
Patent Information
- Application Number
- CN202411668711.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-07
AI Technical Summary
In actual application, the existing polybenzimidazole ion conductive films have problems such as low ionic conductivity and poor alkali stability, and the improvement method will increase the water absorption and swelling rate of the film and reduce mechanical properties.
The ion conductive film is prepared by solution casting method using ternary block polybenzimidazole copolymer resin, and organic solvents are added to form a hydrogen bond cross-linking network to improve the conduction capacity of hydrogen ions or hydroxide ions and solidify. The bath solution is replaced by acid or alkali to form a flow field that facilitates the bidirectional diffusion of the solvent.
It improves the ion conductivity, dimensional stability and acid-base resistance of the membrane, and significantly improves the battery performance.
Smart Images

Figure SMS_1 
Figure QLYQS_4 
Figure QLYQS_7
Abstract
Description
Technical Field
[0001] The invention relates to the field of ion conduction membranes, and in particular to a ternary block polybenzimidazole ion conduction membrane and a preparation method thereof. Background Art
[0002] Polybenzimidazole (PBI) is a heat-stable heterocyclic polymer with a rigid heterocyclic ring in its main chain, which has high thermal and chemical stability. The imidazole group also gives it a unique amphoteric property, allowing it to be acid-doped to produce imidazole cations or base-doped to produce imidazole anions. It can be used in high-temperature resistant fabrics, fire-retardant materials, ion-conducting membranes, etc.
[0003] As an ion-conducting membrane, it can be used in high-temperature fuel cells, water electrolysis to produce hydrogen and its CO2 conversion. However, PBI ion-conducting membranes have problems such as low ion conductivity and poor alkali stability in practical applications. The existing technology mainly introduces ionic groups into polybenzimidazole to increase the density of ionic groups in the membrane, form efficient ion transmission channels, and obtain ion exchange membranes with higher ion exchange capacity. However, this method will increase the water absorption and swelling rate of the membrane and reduce the dimensional stability and mechanical properties of the membrane.
[0004] Due to the different physical and chemical properties of different blocks, block copolymers can form a nanophase-separated structure in the membrane, thereby forming continuous ion nanochannels, which is beneficial to the transport of ions.
[0005] 201910890822.4 discloses a composite high-temperature proton exchange membrane for fuel cells and a preparation method thereof. Block polybenzimidazole and phosphotungstic acid type ionic liquid are respectively dissolved in organic solvents, the two solutions are mixed to obtain a mixed solution, and a film is formed by a casting method to obtain a proton exchange membrane for high-temperature fuel cells.
[0006] ZL201610312227.9 discloses a method for preparing a sulfur-containing polybenzimidazole proton exchange membrane, which is prepared by dissolving a polybenzimidazole block copolymer resin containing a thioether structure in N,N-dimethylacetamide and LiCl (cosolvent and stabilizer) through solution casting. The phosphoric acid doping amount and proton conductivity of the membrane are increased, and the loss of phosphoric acid is slowed down. The thioether structure enables the membrane to quench free radicals, greatly improving the ability to resist free radical oxidation.
[0007] 201710264544.2 discloses a sulfonated polybenzimidazole-polyimide block copolymer composite membrane and its preparation, wherein the sulfonated polybenzimidazole-polyimide block copolymer is dissolved in an organic solvent, directly cast into a polymer membrane at 75-85°C, washed with methanol and 1 mol / L hydrochloric acid in sequence, and then dried to obtain the membrane.
[0008] The membrane made of block polybenzimidazole has a high phosphoric acid doping content, which can improve the proton conductivity of the membrane and is an effective method to improve the performance of polybenzimidazole membranes. However, this method is obtained by improving the structure of polybenzimidazole. Summary of the invention
[0009] The object of the present invention is to provide a ternary block polybenzimidazole conductive membrane, which has high ion conductivity, excellent dimensional stability and acid and alkali resistance stability and excellent battery performance.
[0010] The ternary block polybenzimidazole ion conducting membrane of the present invention is obtained from the ternary block polybenzimidazole copolymer resin by a solution casting method, wherein the solution is prepared by using an organic solvent and adding acid or alkali to dissolve the copolymer resin.
[0011] The ternary block polybenzimidazole copolymer resin is prepared by copolymerizing tetraamine and two different types of carboxylic acid monomers.
[0012] The structural formula of the tetraamine is
[0013] Further, the R1 represents: , , , or .
[0014] Furthermore, R2 in the structural formula represents: O, -CH2, C=O or CH(CH3) 2。
[0015] The two different types of carboxylic acid monomers are dicarboxylic acid A and dicarboxylic acid B.
[0016] Furthermore, the structural formula of the dicarboxylic acid A is or .
[0017] Furthermore, the R3 represents: CF3-C-CF3, CF2-C-CH3.
[0018] Furthermore, the structural formula of the dicarboxylic acid B is , , , , or .
[0019] Another object of the present invention is to provide a method for preparing a ternary block polybenzimidazole ion conducting membrane, comprising the following steps: S1: mixing, heating and dissolving the ternary block polybenzimidazole copolymer resin and a solvent to obtain a copolymer solution; S2 casting the copolymer solution into a liquid film on the surface of the substrate; S3: heating the liquid film, and then placing it in a coagulation bath to coagulate and form a copolymer film; S4 prepares the copolymer membrane by post-treatment.
[0020] According to the present invention, the solvent in step S1 is a mixture of an organic solvent and an acid or a base.
[0021] Furthermore, the acid or base accounts for 1 to 90% of the mass of the mixture.
[0022] Furthermore, the organic solvent is N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone or dimethyl sulfoxide.
[0023] Furthermore, the acid is methanesulfonic acid or concentrated sulfuric acid.
[0024] Furthermore, the alkali is an alkali solution mixture.
[0025] Furthermore, the alkali solution is a mixture of potassium hydroxide or sodium hydroxide and water or alcohol.
[0026] The alcohol is ethanol, n-propanol, isopropanol or n-butanol.
[0027] The potassium hydroxide or sodium hydroxide accounts for 1 to 30% of the mass of the mixture.
[0028] According to the present invention, the copolymer resin in step S1 accounts for 1 to 20% of the mass of the solution.
[0029] According to the present invention, the heating temperature in step S1 is 50-90°C.
[0030] According to the present invention, the heating temperature in step S3 is room temperature to 100°C.
[0031] According to the present invention, the heating time in step S3 is 1 to 100 minutes.
[0032] According to the present invention, the coagulation bath liquid in step S3 is water, ethanol, isopropanol, n-propanol, n-butanol, potassium hydroxide aqueous solution, sodium hydroxide aqueous solution, hydrochloric acid aqueous solution, or any one of the above two.
[0033] Furthermore, the molar ratio of the potassium hydroxide aqueous solution, the sodium hydroxide aqueous solution or the hydrochloric acid aqueous solution is 1 to 10 mol / L.
[0034] According to the present invention, the post-treatment conditions in step S4 are: an acidic system or an alkaline system.
[0035] Furthermore, the acidic system is: 85% phosphoric acid or 1-5 mol / L sulfuric acid aqueous solution, treated at room temperature to 80° C. for 1-24 hours.
[0036] The alkaline system is a 1-5 mol / L potassium hydroxide or sodium hydroxide aqueous solution, and the treatment is carried out at room temperature to 80° C. for 1 to 24 hours.
[0037] Compared with the prior art, the present invention has the following advantages: 1) The present invention selects ternary block polybenzimidazole copolymer resin as raw material. The resin contains different PBI fragments and has different physical and chemical properties. The obtained copolymer membrane can form nanochannels, greatly improving the absorption and conduction of ions, so that the ion conduction membrane has high ion conductivity, excellent dimensional stability and acid and alkali stability and excellent battery performance.
[0038] 2) The present invention uses an organic solvent and an acid or base as a mixed solvent for the copolymer resin. The acid or base contained in the solvent can form a hydrogen bond cross-linking network with the copolymer resin, so that hydrogen ions or hydroxide ions are combined with PBI in the form of covalent cross-linking, thereby improving the copolymer membrane's conductivity for hydrogen ions or hydroxide ions, and hydrogen ions or hydroxide ions will not be lost during use, thereby improving its acid or alkali resistance stability.
[0039] 3) The present invention uses an acid or alkali aqueous solution as a coagulation bath. The acid or alkali coagulation bath can replace the alkali or acid in the copolymer liquid membrane system to form a flow field that is conducive to the two-way diffusion of the solvent. The alkali and acid system is also conducive to the formation of hydrogen ion or hydroxide ion covalent cross-linking in the copolymer membrane, thereby improving the long-term conductivity of the membrane to hydrogen ions or hydroxide ions. DETAILED DESCRIPTION
[0040] A method for preparing a ternary block polybenzimidazole ion conducting membrane comprises the following steps: S1: mixing, heating and dissolving the ternary block polybenzimidazole copolymer resin and a solvent to obtain a copolymer solution; S2 casting the copolymer solution into a liquid film on the surface of the substrate; S3: heating the liquid film, and then placing it in a coagulation bath to coagulate and form a copolymer film; S4 prepares the copolymer membrane by post-treatment.
[0041] According to the present invention, the solvent in step S1 is a mixture of an organic solvent and an acid or a base.
[0042] Furthermore, the acid or base accounts for 1 to 90% of the mass of the mixture.
[0043] Furthermore, the acid or base accounts for 3-60% of the mixture by mass.
[0044] If the dopant content is too low, the dopant is incompatible with the organic solvent mixture system, and the obtained copolymer solution will be stratified; if the dopant content is too high, the dopant will cause the organic solvent to decompose to produce by-products, affecting the stability of the copolymer solution system.
[0045] Furthermore, the acid is methanesulfonic acid or concentrated sulfuric acid.
[0046] Furthermore, the alkali is an alkali solution mixture.
[0047] Furthermore, the alkali solution is a mixture of potassium hydroxide or sodium hydroxide and water or alcohol.
[0048] The alcohol is ethanol, n-propanol, isopropanol or n-butanol.
[0049] The potassium hydroxide or sodium hydroxide accounts for 1 to 30% of the mass of the mixture.
[0050] According to the present invention, the copolymer resin in step S1 accounts for 1 to 20% of the mass of the solvent.
[0051] Preferably, the copolymer resin accounts for 3-12% of the mass of the solvent.
[0052] If the copolymer resin content is too low, the obtained copolymer solution is dilute and the copolymer film strength is low. If the copolymer resin content is too high, it is not conducive to its dissolution in the solvent.
[0053] According to the present invention, the heating temperature in step S1 is 50-90°C.
[0054] According to the present invention, the heating temperature in step S3 is room temperature to 100°C.
[0055] Furthermore, the heating temperature is 40-80°C.
[0056] The heating temperature affects the diffusion rate of the solvent in the copolymer liquid film and the pore structure of the membrane surface. If the temperature is too high, the alcohol solvent evaporates quickly and a thin and dense skin layer can be formed quickly. If the temperature is too low, the film formation time is long and the surface skin structure is affected.
[0057] According to the present invention, the coagulation bath liquid in step S3 is water, ethanol, isopropanol, n-propanol, n-butanol, potassium hydroxide aqueous solution, sodium hydroxide aqueous solution, hydrochloric acid aqueous solution, or any one of the above two.
[0058] Selecting potassium hydroxide aqueous solution, sodium hydroxide aqueous solution or hydrochloric acid aqueous solution as the coagulation bath liquid can replace the acid or alkali in the copolymer liquid membrane system to form a flow field that is conducive to the two-way diffusion of the solvent. The alkali and acid systems are also conducive to the formation of hydrogen ion or hydroxide ion covalent cross-linking in the copolymer membrane, thereby improving the long-term conductivity of the membrane to hydrogen ions or hydroxide ions.
[0059] According to the present invention, the post-treatment conditions in step S4 are: an acidic system or an alkaline system.
[0060] Furthermore, the acidic system is: 85% phosphoric acid or 1-5 mol / L sulfuric acid aqueous solution, treated at room temperature to 100° C. for 1-24 hours.
[0061] The alkaline system is a 1-5 mol / L potassium hydroxide or sodium hydroxide aqueous solution, and the treatment is carried out at room temperature to 80° C. for 1 to 24 hours.
[0062] Comparative Example 1 1.8g of ternary block polybenzimidazole copolymer resin and 13.2g of N,N-dimethylacetamide were mixed and stirred at 60°C to obtain a copolymer solution; the solution was filtered and degassed and then cast on a glass plate to obtain a copolymer liquid film; the liquid film was placed at 80°C for 1 minute, and then placed in a 1mol / L hydrochloric acid aqueous solution to solidify and form a copolymer membrane; the copolymer membrane was treated in a 3mol / L potassium hydroxide aqueous solution at 60°C for 4 hours to obtain a ternary block polybenzimidazole copolymer ion conduction membrane. The membrane thickness is 150µm, OH - The conductivity is 48.1mS / cm and the swelling rate is 20.3%.
[0063] Example 1 1.8g of ternary block polybenzimidazole copolymer resin, 0.1g of potassium hydroxide, 0.3g of n-propanol and 12.8g of N,N-dimethylacetamide were mixed and stirred at 60°C to obtain a copolymer solution; the solution was filtered and degassed and then cast on a glass plate to obtain a copolymer liquid film; the liquid film was placed at 80°C for 1 minute, and then placed in a 1mol / L hydrochloric acid aqueous solution to solidify and form a copolymer membrane; the copolymer membrane was treated in a 3mol / L potassium hydroxide aqueous solution at 60°C for 4 hours to obtain a ternary block polybenzimidazole copolymer ion conduction membrane. The membrane thickness is 150µm, OH - The conductivity is 95.4mS / cm and the swelling rate is 22.6%.
[0064] Example 2 0.45g of ternary block polybenzimidazole copolymer resin, 1.31g of sodium hydroxide, 3.05g of water and 10.19g of N,N-dimethylformamide were mixed and stirred at 50°C to obtain a copolymer solution; the solution was filtered and degassed and then cast on an aluminum sheet to obtain a copolymer liquid film; the liquid film was placed at 80°C for 5 minutes, and then placed in a 5% isopropanol aqueous solution to solidify and form a copolymer membrane; the copolymer membrane was treated in a 6mol / L potassium hydroxide aqueous solution at 40°C for 6 hours to obtain a ternary block polybenzimidazole copolymer ion conduction membrane. The membrane thickness is 150µm, OH -The conductivity is 178.5mS / cm and the swelling rate is 28.4%.
[0065] Example 3 1.35g of ternary block polybenzimidazole copolymer resin, 8.19g of methanesulfonic acid and 5.46g of N-methylpyrrolidone were mixed and stirred at 70°C to obtain a copolymer solution; the solution was filtered and degassed and then cast on a polyester film to obtain a copolymer liquid film; the liquid film was placed at 40°C for 100 minutes, and then placed in a 1mol / L potassium hydroxide aqueous solution to solidify and form a copolymer membrane; the copolymer membrane was treated at 100°C and 85% phosphoric acid for 10 hours to obtain a ternary block polybenzimidazole copolymer ion conduction membrane. The membrane thickness is 150µm, H + The conductivity is 264.8mS / cm and the swelling rate is 24.3%.
[0066] Example 4 0.75g of ternary block polybenzimidazole copolymer resin, 5.7g of sulfuric acid and 8.55g of dimethyl sulfoxide were mixed and stirred at 90°C to obtain a copolymer solution; the solution was filtered and degassed and then cast on a glass plate to obtain a copolymer liquid film; the liquid film was placed at 50°C for 40 minutes, and then placed in a 20% dimethyl sulfoxide aqueous solution to solidify and form a copolymer membrane; the copolymer membrane was treated in a 3mol / L sodium hydroxide aqueous solution at 80°C for 6 hours to obtain a ternary block polybenzimidazole copolymer ion conduction membrane. The membrane thickness is 150µm, OH - The conductivity is 141.3mS / cm and the swelling rate is 26.9%.
Claims
1. A ternary block polybenzimidazole ion conducting membrane, characterized in that: The invention is obtained by solution casting from ternary block polybenzimidazole copolymer resin, wherein the solution is prepared by using organic solvent and adding acid or alkali to dissolve the copolymer resin.
2. The method for preparing the ternary block polybenzimidazole ion conducting membrane according to claim 1, characterized in that: The following steps are involved: S1: mixing, heating and dissolving the ternary block polybenzimidazole copolymer resin and a solvent to obtain a copolymer solution; S2 casting the copolymer solution into a liquid film on the surface of the substrate; S3: heating the liquid film, and then placing it in a coagulation bath to coagulate and form a copolymer film; S4 prepares the copolymer membrane by post-treatment.
3. The preparation method according to claim 2, characterized in that: The ternary block polybenzimidazole copolymer resin in step S1 is obtained by copolymerizing a tetraamine and two different types of carboxylic acid monomers; Furthermore, the structural formula of the tetraamine is ; Furthermore, the R1 represents: , , , , ; Still further, said R2 represents: O, -CH2, C=O or CH(CH3)2; The two different types of carboxylic acid monomers are dicarboxylic acid A and dicarboxylic acid B; Furthermore, the structural formula of the dicarboxylic acid A is or ; Furthermore, the R3 represents: CF3-C-CF3, CF2-C-CH3; Furthermore, the structural formula of the dicarboxylic acid B is , , , , or .
4. The preparation method according to claim 2, characterized in that: The solvent in step S1 is a mixture of an organic solvent and an acid or a base.
5. The preparation method according to claim 4, characterized in that: The acid or base accounts for 1 to 90% of the mass of the mixture; the organic solvent is N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone or dimethyl sulfoxide; the acid is methanesulfonic acid or concentrated sulfuric acid; and the base is a lye mixture.
6. The preparation method according to claim 5, characterized in that: The alkali solution is a mixture of potassium hydroxide or sodium hydroxide and water or alcohol.
7. The preparation method according to claim 6, characterized in that: The alcohol is ethanol, n-propanol, isopropanol or n-butanol; the potassium hydroxide or sodium hydroxide accounts for 1 to 30% of the mixture by mass.
8. The preparation method according to claim 2, characterized in that: The copolymer resin in step S1 accounts for 1 to 20% of the mass of the solution; the heating temperature in step S1 is 50 to 90° C.; the heating temperature in step S3 is room temperature to 100° C.; the heating time in step S3 is 1 to 100 min; the coagulation bath in step S3 is water, ethanol, isopropanol, n-propanol, n-butanol, potassium hydroxide aqueous solution, sodium hydroxide aqueous solution, hydrochloric acid aqueous solution and any one of the above two; the post-treatment conditions in step S4 are: an acidic system or an alkaline system.
9. The preparation method according to claim 8, characterized in that: The molar ratio of the potassium hydroxide aqueous solution, the sodium hydroxide aqueous solution or the hydrochloric acid aqueous solution is 1 to 10 mol / L.
10. The preparation method according to claim 8, characterized in that: The acidic system is: 85% phosphoric acid or 1-5 mol / L sulfuric acid aqueous solution, treated at room temperature to 80° C. for 1-24 hours; the alkaline system is 1-5 mol / L potassium hydroxide or sodium hydroxide aqueous solution, treated at room temperature to 80° C. for 1-24 hours.
Citation Information
Patent Citations
Preparation method of novel sulfur-containing polybenzimidazole proton exchange membrane
CN105895944A
Ternary block copolymerized polybenzimidazole, high-temperature proton exchange membrane and preparation methods of ternary block copolymerized polybenzimidazole and high-temperature proton exchange membrane
CN116606439A
Polybenzimidazole ion conducting membrane and preparation method thereof
CN117887256A
Preparation method of polybenzimidazole proton exchange gel membrane
CN118546412A
Polybenzimidazole with protecting groups, preparation method for membrane using the same and use thereof
WO2023167545A1